Measurement of Supply Chain Management Performance with the Supply Chain Operating References (SCOR) Method at PT. XYZ - Annisa, Nur; Sri Zuliarni (ABEC Indonesia, 2024)
Amidst the competition of manufacturing industry in Batam City, every company must have a strategy tocreate effective and efficient supply chain performance. PT XYZ is a manufacturing company that produces lift-ing/transporting equipment based on customer requests. This research aims to provide performance indicators (KPIs) foreach supply chain process and provide performance measurement of supply chain management performance at PT XYZwhich will be followed by improvement recommendations to improve performance. Performance measurement is usingthe SCOR method from filling out a questionnaire which is then validated and then calculated the weighting value usingAHP and normalization using the SNORM de Boer method for the final result of supply chain performance. The resultsof the assessment of the supply chain performance of PT XYZ are rated in the Average category. In order for the supplychain management performance to be optimal, it is necessary to improve and improvise supply chain management byconducting detailed demand analysis, improving inventory management, and streamlining the flow of information onreceiving customer returns.